Improving Students’ Reading Comprehension through Mind Mapping (The Case at Grade IX of SMPN 2 Surakarta) - Ninda Mayada Ertha; Ema Butsi Prihastari; Yuyun Yuniarti (Journal of Advanced Multidisciplinary Research, 2025)
Reading comprehension is vital in English language learning, especially in EFL contexts. One core sub-skill—making inferences—remains a significant challenge for many students. Using the Mind Mapping technique, this study aimed to improve students' inference-making abilities in reading narrative texts. This Classroom Action Research (CAR) was conducted in two cycles, utilizing Kemmis and McTaggart’s planning, action, observation, and reflection. The study involved 32 ninth-grade students of SMPN 2 Surakarta in the even semester of 2025. Data were collected through pre-tests, post-tests, observation sheets, field notes, and student questionnaires. The results revealed a significant improvement in students' reading comprehension, with the average score rising from 68,37 in the pre-test to 77.06 in Post-Test 1 and 84.19 in Post-Test 2, with a 9.25% increase. Furthermore, 87.5% of students met the Minimum Mastery Criterion (KKM), which was set at 80, fulfilling the success criteria of the CAR. Students’ ability to make inferences and their classroom engagement also improved. The findings indicate that mind mapping effectively enhances students’ comprehension of narrative texts, fosters motivation, and encourages active participation in reading activities.